Integrating self-efficacy reinforcement into problem-based learning enhances critical creative and communicative skills - Indra Sabdarudin; Al Rafni; Suryanef Suryanef; Hasrul Hasrul (Global Econedu, 2026)
This study aimed to examine the effect of Problem-Based Learning (PBL) integrated with self-efficacy reinforcement on students' critical thinking, creative thinking, and communicative skills in Civic Education. A quantitative quasi-experimental design with a pretest–posttest nonequivalent control group was employed involving 68 tenth-grade students divided into experimental (n = 34) and control (n = 34) groups. Data were collected using critical thinking essay tests, observation rubrics for creative thinking and communicative skills, and a self-efficacy questionnaire. The data were analyzed using paired-samples t-tests, independent-samples t-tests, normalized gain (N-Gain), and MANOVA. The experimental group demonstrated significantly greater improvements than the control group in critical thinking (N-Gain = 60.81%), creative thinking (59.09%), and communicative skills (54.65%). MANOVA indicated a significant multivariate effect (F = 44.285, p < 0.001; Pillai's Trace = 0.675), while students also exhibited high self-efficacy across all measured dimensions. Integrating self-efficacy reinforcement into PBL effectively enhances higher-order thinking and communicative competencies, providing an effective instructional approach for developing twenty-first-century skills in secondary Civic Education